Implementation of algorithm to determine estimated state of charge, travelling time and distance to cover for electrically powered vehicle - Saha, Aparna; Anjum, Murshida; Md. Arefin, Dewan Abu; Taif, Mir Rayhanuzzaman (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.